Answer:
(x+4)
Step-by-step explanation:
2x + 3y + 2(x - y) - 3x
First you apply the distributive property:
2x +3y + 2(x) - 2(y) - 3x
2x + 3y +2x - 2y - 3x
The you combine like terms:
2x + 2x - 3x +3y - 2y
4x - 3x + y
x (x could also be 1x) + y (y could also be 1y)
The answer is x + y or 1x + 1y
3x^0 (2x^3y^2)^4
--------------------------
(4x^7y^4) ^2
= 3 * 1 (2x^3y^2)^4
-------------------------- Zero Exponent Property X^0 =1
(4x^7y^4) ^2
3 (2^4 *x^3*4 y^2*4)
-------------------------- power of a power property x^a ^b = x^(a*b)
4^2 x^7*2 y^4*2
3 *16 *x^12 y^8
-------------------------- simplify
16 x^14 y^8
3 *x^12 y^8
-------------------------- simplify
x^14 y^8
3 *x^(12-14) y^(8-8)
-------------------------- Quotient of Power X^a/ X^b = X^ (a-b)
3x^-2 y^0 simplify
3x^-2 *1 Zero Exponent Property X^0 =1
3 / x^2 Negative exponent property x^-a = 1/x^a
Answer:
A is the answer
Step-by-step explanation:
The steps are duplicated.Then, first I will write the steps in the right form:
19 = 5x - 1
20 = 5x
4 = x
Now, I will write the steps with the justification
19 = 5x - 1.... start
20 = 5x ..... Reason: addtion property of equality (you get this by adding +1 to both sides of the previous equality)
4 = x .... Reason: division property of equality (you get this by dividing by 5 both sides of the previous equality)